2004
DOI: 10.1099/vir.0.19706-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of VPg-Pro of Turnip mosaic virus with the translation initiation factor 4E and the poly(A)-binding protein in planta

Abstract: The viral protein linked to the genome (VPg) of Turnip mosaic virus (TuMV) interacts in vitro with the translation eukaryotic initiation factor (eIF) 4E. In the present study, we investigated the consequence of TuMV infection on eIF4E expression. Two isomers are present in plants, namely eIF4E and eIF(iso)4E. Expression of the latter was detected in both TuMV-infected and mock-inoculated Brassica perviridis plants, but expression of eIF4E was found only in infected plants. Membranes from TuMV-infected or mock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 65 publications
5
87
0
Order By: Relevance
“…These studies suggest that VPg may recruit the ribosome to the genomic RNA through interaction with the canonical translation initiation factors. A similar role has also been described for the VPg proteins from the Nepoviridae and Potyviridae (38)(39)(40)(41). Moreover, the observations that protease K treatment to remove VPg from astrovirus RNA renders the viral RNA noninfectious and that infectivity can be restored to RNA transcripts by addition of a 5= m 7 G cap are consistent with a role for astroviral VPg in translation (28,42).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…These studies suggest that VPg may recruit the ribosome to the genomic RNA through interaction with the canonical translation initiation factors. A similar role has also been described for the VPg proteins from the Nepoviridae and Potyviridae (38)(39)(40)(41). Moreover, the observations that protease K treatment to remove VPg from astrovirus RNA renders the viral RNA noninfectious and that infectivity can be restored to RNA transcripts by addition of a 5= m 7 G cap are consistent with a role for astroviral VPg in translation (28,42).…”
supporting
confidence: 65%
“…In FCV VPg, the helix ␣2 sequence 40 VEDFLMLRHRA AL 52 is replaced in the MNV protein by 42 IDDYLADREREEELL 56 ( Fig. 3A), which contains many more charged residues.…”
Section: Discussionmentioning
confidence: 99%
“…A yeast two-hybrid screen has shown that eIF(iso)4E of Arabidopsis thaliana interacts with the VPg of Turnip mosaic virus (TuMV) (57). This interaction (31) has also been reported to take place in infected cells (32). Similar interactions are taking place between the VPg of other potyviruses and either eIF(iso)4E or eIF4E (20,46).…”
mentioning
confidence: 61%
“…Higher RNA and VPg levels of replicating viruses may require more P0 and eIF4E/eIF(iso)4E, making their translation more sensitive to silencing of these proteins. P0 transcription is induced early in PVA infection (66), and TuMV infection upregulates eIF4E (67), suggesting that the demand for these proteins is increased during natural potyvirus infection. This was supported by results showing that the silencing of both of these host factors reduced PVA infection similarly (Fig.…”
Section: Fig 10mentioning
confidence: 99%